The Role Of Formal And Non-Formal Language Environments In Modern Islamic Boarding School In Improving Students' Arabic Speaking Ability: دورالبيئة اللغوية المنهجية واللامنهجية في المعاهد الحديثة في تعزيز مهارة الكلام باللغة العربية لدى الطلاب - Zein, M. Dimas Suhaimi; Padli Nasution, Muhammad Irwan (Ukazh : Journal of Arabic Studies, 2025)
This study aims to analyze the implementation of the language environment, both formal and non-formal, and its role in improving students' Arabic speaking skills at the Modern Islamic Boarding School of MTs Muhammadiyah Sidomulyo Langkat. This study uses a qualitative approach with a case study type, and data is collected through triangulation techniques, namely by observation, in-depth interviews, and documentation. The results of the study indicate that the development of Arabic speaking skills does not only depend on formal learning in the classroom, but is also greatly influenced by non-formal activities that shape the language culture at the boarding school. The formal environment provides a linguistic foundation and language structure through learning muhadatsah, qira'ah, insya', nahwu, and shorof, while non-formal environments such as ilqa' al-kalimah, daily muhadatsah, language weeks, and language patrols foster courage, habits, and fluency in speaking. The synergy between the two environments creates a conducive and sustainable language ecosystem. These results strengthen Krashen's theory of second language acquisition which emphasizes the importance of meaningful input and communicative interaction in a positive emotional atmosphere (low affective filter). This research provides a theoretical contribution to the development of an environment-based Arabic language learning model in creating a communicative and sustainable language culture.